Expectations and adjustment dynamics in a two-sector model of a small open economy - Max Albert; Jürgen Meckl (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1991)
This paper generalizes the analysis in Albert (1989) and Meckl (1990) of adjustment in a dynamic specific-factors model with endogenous capital stocks. Capital reallocation and accumulation are consequences of investment decisions and depreciation. The Investment process is analyzed under a spectrum of expectations which include rational, adaptive, and static expectations as special cases. Only with rational expectations the speed of adjustment is optimal; adjustment is too fast if expectations are biased towards the status quo, and too slow if expectations are biased towards long-run values. Local and global analysis of the adjustment path show sharp qualitative differences. Non-monotonic adjustment of capital stocks and the social product is possible and is not necessarily the result of expectational errors.
Keywords: 330; Erwartungstheorie; Wirtschaftliche Anpassung; Offene Volkswirtschaft; Theorie